Optimization conditions, antibacterial and antioxidant activities of clitopilus chalybescens - Jatuwong, Kritsana; Hyde, Kevin D; Chamyuang, Sunita; Matsui, Kenji; Kakumyan, Pattana (Asia-Pacific Journal of Science and Technology, 2016)
The aim of this work was to study the effect of media, temperature and pH on the mycelial growth of Clitopilus chalybescens strain MFLUCC 13–0809 collected from Lampang, Thailand. The antioxidant and antibacterial activities from the crude mycelial extracts were evaluated. The study indicated that the optimal medium, pH and temperature were observed on yeast extract agar (YEA) pH 5 to 7, and 20–29˚C, respectively. For antibacterial activities, crude extracts from mycelium slightly inhibited the growth of Gram positive bacteria (Bacillus subtilis, Staphylococcus aureus and Micrococcus luteus), but no activities were observed on Gram negative bacteria (Pseudomonas aeruginosa and Escherichia coli). Antioxidant assay indicated that the crude extract had noticeable scavenging activity on 2,2-diphenyl-1 picrylhydrazyle (DPPH) radical. The results suggest that the crude extract from this mushroom mycelium deem to have a potential for further development on antibacterial and antioxidant applications.